Potential New Therapies for Pediatric Diffuse Intrinsic Pontine Glioma - Wenyong Long; Yang Yi; Yang Yi; Shen Chen; Shen Chen; Qi Cao; Wei Zhao; Wei Zhao; Qing Liu (Frontiers Media S.A., 2017)
Diffuse intrinsic pontine glioma (DIPG) is an extensively invasive malignancy with infiltration into other regions of the brainstem. Although large numbers of specific targeted therapies have been tested, no significant progress has been made in treating these high-grade gliomas. Therefore, the identification of new therapeutic approaches is of great importance for the development of more effective treatments. This article reviews the conventional therapies and new potential therapeutic approaches for DIPG, including epigenetic therapy, immunotherapy, and the combination of stem cells with nanoparticle delivery systems.